'Interactive evaluation' of an e-learning course within the context of blended education. (2017) - Laskaris, Dimitris; Kalogiannakis, Michail; Heretakis, Emmanuel
The focus of this paper is the evaluation of an online course designed and developed within the context of blended learning for the Department of Communication and Media of the University of Athens. The course was based on the principles of distance learning; it utilised the open-source learning management system - Moodle, and it was implemented as an action research project for three consecutive semesters (2014-2016). Its pedagogical aim was to investigate a prototype model of digital learning: the 'interactive evaluation' that was embodied in the design of the e-course and in the cycles of action research. Acting as creators, teachers and researchers in order to investigate the student-evaluators' perceptions of the e-course, we attempted to 'produce' wider knowledge of the assessment criteria within the context of blended education. In particular, the how and why specific learning criteria and critical approach to knowledge can be organised as more general constructivist and student-centred indexes of the learning technology. As a case study, the research outcomes revealed factors related to expression of interest, encouragement for participation and motivation of students to infiltrate, evaluate the e-course and contribute to remodelling its educational material.